2020
DOI: 10.1111/dom.14110
|View full text |Cite
|
Sign up to set email alerts
|

The novel dual glucose‐dependent insulinotropic polypeptide and glucagon‐like peptide‐1 (GLP‐1) receptor agonist tirzepatide transiently delays gastric emptying similarly to selective long‐acting GLP‐1 receptor agonists

Abstract: The effect of dual glucose‐dependent insulinotropic polypeptide (GIP) and glucagon‐like peptide‐1 (GLP‐1) receptor agonist (RA) tirzepatide on gastric emptying (GE) was compared to that of GLP‐1RAs in non‐clinical and clinical studies. GE was assessed following acute and chronic treatment with tirzepatide in diet‐induced obese mice versus semaglutide or long‐acting GIP analogue alone. Participants [with and without type 2 diabetes (T2DM)] from a phase 1, 4‐week multiple dose study received tirzepatide, dulaglu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
80
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(84 citation statements)
references
References 16 publications
3
80
1
Order By: Relevance
“…Since gastric emptying effects with long-acting GLP-1 agonists attenuate over time (Umapathysivam et al, 2014;Urva et al, 2020), we believe this phenomenon will not play a significant role in long-term glucose control, and the insulinotropic character of the three involved principles will become the major driving force for glucose control.…”
Section: Ll Open Accessmentioning
confidence: 99%
“…Since gastric emptying effects with long-acting GLP-1 agonists attenuate over time (Umapathysivam et al, 2014;Urva et al, 2020), we believe this phenomenon will not play a significant role in long-term glucose control, and the insulinotropic character of the three involved principles will become the major driving force for glucose control.…”
Section: Ll Open Accessmentioning
confidence: 99%
“…However, the mechanism of the I-M-150847-mediated regulation of the gut-brain axis is presently unexplored. Reduced gastric emptying and delayed intestinal motility have been reported in the case of long-acting GLP-1R agonists (48) as well as GLP-1R GIPR dual agonist Tirzepatide (49).GIPR is present in key feeding centers at the hypothalamus and intracerebroventricular administration of acyl GIP causes acute neural activation in the feeding centers that includes the arcuate nucleus, dorsomedial hypothalamic nucleus, ventromedial nucleus of the hypothalamus, and lateral hypothalamus (50). Future research is needed to explore whether I-M-150847 causes similar neural activity in the feeding centers to trigger early induction of satiety.…”
Section: Discussionmentioning
confidence: 99%
“…When compared with semaglutide 1.0 mg, GI adverse effects were slightly more common with the highest dose of terzipatide (15 mg) (table 1). Nausea and vomiting are attributed in part to delay in gastric emptying, which usually subsides after several weeks [17]. In fact, Urva et al [17] have shown that tirzepatide caused delay in gastric emptying that was similar in magnitude to the selective GLP-1 agonist dulaglutide.…”
Section: Gastrointestinal Adverse Effectsmentioning
confidence: 99%